Three and Four Membered Heterocyclic Rings Substituted Derivatives of Phenobarbital and Using CPE for Determination of PB (II) - Ali Jassim Al-Zuhairi (Journal of Global Pharma Technology, 2018)
A series of three and four member rings N-substituted Phenobarbital have been synthesized. The nitrogen atoms have been alkylated first to form N-carboxymethyl followed by cyclization reaction to form three and four heterocyclic rings. All the synthesized compounds have been identified using I.R, 1H NMR, and then using its heterocyclic rings by determination of lead (II) by cloud point extraction (CPE) techniques. Keywords: 5, 5-substituted Phenobarbital, 1, 2-Diazetidine, 1,2-diaziridin, Cloud point extraction, Triton X-114.